Semiotic Analysis Of The HYMN and March Of UIN Ar-Raniry: A Charles Morris Perspective - Zacky Aqsha Noriska; Zulhelmi; Cut Oriza Satifa; Sahri Wanara; Urwatil Wusqa (Kopula: Jurnal Bahasa, Sastra, dan Pendidikan, 2026)
This study aims to reveal the implementation of Islamic law based education at UIN Ar-Raniry Banda Aceh as reflected in the lyrics of the UIN Ar-Raniry Hymn and March. This research employs a qualitative method using Charles Morris’s semiotic theory as the analytical framework. Data were collected through reading and note-taking techniques within a literature-based study. The data were analyzed using a descriptive-analytical method. The findings indicate that the Hymn and March of UIN Ar-Raniry represent the implementation of an Islamic law based education system at UIN Ar-Raniry, characterized by the integration of Islamic and general sciences, the internalization of Islamic law values, and the establishment of faculties that combine both domains of knowledge. UIN Ar-Raniry is committed to producing graduates who are spiritually and intellectually excellent and well prepared to actively participate in national and civic life. The implementation of Islamic law based education is expected not to be limited to UIN Ar-Raniry alone, but also to be adopted by other educational institutions, particularly in Aceh. The further development and sustainability of this Islamic law based education require continuous support from various stakeholders in order to realize a globally competitive vision of Islamic education.